Taniec Dawida – małżeństwo a wiara - Basiuk, Maciej (Studia Pastoralne, 2026)
The first marriage of David had been eventful from the very beginning. It reached a dramatic climax when Michal despised her husband because of his dance during transportation of the Ark to Jerusalem. This article examines how an act of devotion (David’s dance) may influence the relationship between spouses.